Interobserver reliability of rheumatologists performing musculoskeletal ultrasonography: results from a EULAR "Train the trainers" course. Issue 7 (7th January 2005) - Scheel, A K; Schmidt, W A; Hermann, K-G A; Bruyn, G A; D'Agostino, M A; Grassi, W; Iagnocco, A; Koski, J M; Machold, K P; Naredo, E; Sattler, H; Swen, N; et al.
Abstract : Objective: To evaluate the interobserver reliability among 14 experts in musculoskeletal ultrasonography (US) and to determine the overall agreement about the US results compared with magnetic resonance imaging (MRI), which served as the imaging "gold standard". Methods: The clinically dominant joint regions (shoulder, knee, ankle/toe, wrist/finger) of four patients with inflammatory rheumatic diseases were ultrasonographically examined by 14 experts. US results were compared with MRI. Overall agreements, sensitivities, specificities, and interobserver reliabilities were assessed. Results: Taking an agreement in US examination of 10 out of 14 experts into account, the overall κ for all examined joints was 0.76. Calculations for each joint region showed high κ values for the knee (1), moderate values for the shoulder (0.76) and hand/finger (0.59), and low agreement for ankle/toe joints (0.28). κ Values for bone lesions, bursitis, and tendon tears were high (κ = 1). Relatively good agreement for most US findings, compared with MRI, was found for the shoulder (overall agreement 81%, sensitivity 76%, specificity 89%) and knee joint (overall agreement 88%, sensitivity 91%, specificity 88%). Sensitivities were lower for wrist/finger (overall agreement 73%, sensitivity 66%, specificity 88%) and ankle/toe joints (overall agreement 82%, sensitivity 61%, specificity 92%). Conclusion: Interobserver reliabilities, sensitivities, and specificities in comparison with MRI were moderate to good. Further standardisation of US scanning techniques and definitions of different pathological US lesions are necessary to increase the interobserver agreement in musculoskeletal US.